Flora of Bokor National Park VII: Thismia bokorensis (Burmanniaceae), a new species representing a new generic record - Suetsugu, Kenji; Tsukaya, Hirokazu; Tagane, Shuichiro; Chhang, Phourin; Yukawa, Tomohisa; Yahara, Tetsukazu (Phytotaxa, 2018)
The genus Thismia Griffith (1844: 221) of the tribe Thismieae, Burmanniaceae sensu APG IV (2016) or Thismiaceae of other authors, represents one of the most species-rich mycoheterotrophic genera and consists of more than 60 species (Jonker 1948, Merckx 2008). Considering that the majority of these species were collected only once (Jonker 1948), and that many new species have recently been discovered, especially from various Southeast Asian countries (e.g., Tsukaya & Okada 2012, Dančák et al. 2013, Nuraliev et al. 2014, 2015, Truong et al. 2014, Chantanaorrapint & Sridith 2015, Li & Bi 2013, Hroneš et al. 2015, Tsukaya et al. 2017, Suetsugu et al. 2017), many more undescribed species are probably still hidden in the tropical rain forests of Southeast Asia.